Outcomes of Laparoscopy-assisted Distal Gastrectomy - Yasuda, Kazuhiro; Inomata, Masahumi; Shiraishi, Norio; Kitano, Seigo; Adachi, Yosuke (Nippon Shokaki Geka Gakkai zasshi, 2001)
Since 1991, we have successfully treated 81 patients with early gastric cancer using laparoscopy-assisted distal gastrectomy (LADG) with regional lymph nodes (n1) dissection. Indications for LADG in the distal portion of the stomach are (1) mucosal cancer (>10 mm for depressed lesions), (2) mucosal cancer (>20 mm for protruding lesions), (3) mucosal cancer with ulceration scars, and (4) submucosal cancer with slight invasion. Our 81 subjects underwent LADG because mucosal cancers were large or involved ulceration scars (59%) or because submucosal cancer involved slight invasion (20%). The average operating time was 234 min and average bleeding volume 141 ml. The only 3 complications were pneumonia, anastmotic stenosis, and pancreatic juice leakage, all treated conservatively. Although only 3 cases involved perigastric lymph node metastasis, histological examinations of resected specimens revealed all surgeries were curative. All patients undergone LADG were alive without recurrence or port-site metastasis during follow-up period from 6 to 98 months. Our historical study, as reported previously, showed LADG has such advantages as less surgical trauma, less impaired nutrition, less pain, rapid retum of gastrointestinal function, shorter hospital stay, and better quality of life, all with no decrease in operative curability. LADG is thus safe and useful in patients with early gastric cancer.